Mass shootings and gun violence in America: issues and perspectives - Zandler, John C. (Law, crime and law enforcement, 2013)
Public mass shootings in the United States : selected implications for federal public health and safety policy Jerome P. Bjelopera, Erin Bagalman, Sarah W. Caldwell, Kristin M. Finklea and Gail McCallion -- Now is the time : the President's plan to proect our children and our communities by reducing gun violence White House staff -- Statement of Senator Patrick Leahy, chairman, Senate Judiciary Committee : hearing on "What should America do about gun violence?" -- Statement of Senator Orrin G. Hatch : hearing on "What should America do about gun violence?" -- Statement of Senator Ted Cruz : hearing on "What should America do about gun violence?" -- Testimony of Captain Mark Kelly, Americans for Responsible Solutions : hearing on "What should America do about gun violence?" -- Testimony of David B. Kopel, adjunct professor of advanced constitutional law, Denver University : hearing on "What should America do about gun violence?" -- Testimony of Chief Jim Johnson, Baltimore County Policy Department : hearing on "What should America do about gun violence?" -- Testimony of Gayle S. Trotter, senior fellow, Independent Women's Forum : hearing on "What should America do about gun violence?" -- Testimony of Wayne LaPierre, executive vice president, National Rifle Association : hearing on "What should America do about gun violence?" -- Statement of Senator Patrick Leahy, chairman, Senate Judiciary Committee : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Statement of Senator Orrin G. Hatch : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Statement of Senator Ted Cruz : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Statement of Senator Timothy J. Heaphy, U.S. attorney, Department of Justice : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Testimony of Laurence H. Tribe, Carl M. Loeb University Professor, Harvard Law School : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Testimony of Daniel W. Webster, professor and director, Johns Hopkins Center for Gun Policy and Research : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Testimony of Sandra J. Wortham : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Statement of Charles J. Cooper, partner, Cooper & Kirk, PLLC : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment" -- Testimony of Suzanna Hupp : hearing on "Proposal to reduce gun violence : protecting our communities while respecting the Second Amendment